Photon diffusion near the point-of-entry in anisotropically scattering turbid media - Vitkin, Edward; Turzhitsky, Vladimir; Qiu, Le; Guo, Lianyu; Itzkan, Irving; Hanlon, Eugene B.; Perelman, Lev T. (Nature communications, 2011)
From astronomy to cell biology, the manner in which light propagates in turbid media has been of central importance for many decades. However, light propagation near the point-of-entry in turbid media has never been analytically described, until now. Here we report a straightforward and accurate method that overcomes this longstanding, unsolved problem in radiative transport. Our theory properly treats anisotropic photon scattering events and takes the specific form of the phase function into account. As a result, our method correctly predicts the spatially dependent diffuse reflectance of light near the point-of-entry for any arbitrary phase function. We demonstrate that the theory is in excellent agreement with both experimental results and Monte Carlo simulations for several commonly used phase functions. Optical imaging and spectroscopy rely on understanding how light enters and propagates through turbid media, yet its behaviour near the point-of-entry has remained elusive. Now Vitkin et al . report an analytical solution to this problem and demonstrate its agreement with simulations and experiments.